2022
DOI: 10.3390/agriculture12101513
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of Pneumatic Downforce Regulating Device for No-Till Corn Planter

Abstract: To avoid the issues of undesired soil compaction and seeding depth variation caused by the downforce fluctuation of the corn no-till planter, the influence of the structural parameters of the air spring on the downforce was researched in this paper, by establishing the gas–solid coupling simulation model of the air spring. The downforce test bench was built to verify the simulation model; the test showed that the vertical output force error of the simulation model was 4.79%, the pitch diameter error was 0.76%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The upper two bars of the parallelogram system have been provided with seven steps to change the spring tension. A downforce higher than 600 N is required to achieve better uniformity in depth [ 27 ]; the dead weight of the hinged row unit and spring tension force must reach this value. The dead weight of the hinged part of a row unit is 382.32 N and the remaining force of 217.68 N is required to be supplied by spring tension.…”
Section: Methodsmentioning
confidence: 99%
“…The upper two bars of the parallelogram system have been provided with seven steps to change the spring tension. A downforce higher than 600 N is required to achieve better uniformity in depth [ 27 ]; the dead weight of the hinged row unit and spring tension force must reach this value. The dead weight of the hinged part of a row unit is 382.32 N and the remaining force of 217.68 N is required to be supplied by spring tension.…”
Section: Methodsmentioning
confidence: 99%
“…The ABAQUS finite element simulation has been widely used to simulate and analyze the mechanical characteristics of air springs in high-speed trains, buses, and heavy trucks, and its modeling effectiveness and accuracy have been verified many times [25,26] . Meanwhile, before the research of this article, the vertical force, pitch diameter, and internal pressure of the simulation model and the physical model have been verified in detail in the previous research [27] .…”
Section: Simulation Analysis and Parameter Optimizationmentioning
confidence: 99%
“…Zhou et al designed an active adjustment system for sowing depth based on air springs and Flex sensors, which reduced the error by 40% compared with passive adjustment [60]. In order to reduce the influence of downforce on furrowing depth, Cao et al identified the critical parameters of the air spring that had a significant influence on the downforce according to gas-solid coupling simulation and optimized the key parameters to improve the stability of the furrowing depth of pneumatic active profiling adjusting device [61]. The pneumatic-driven downforce adjustment device has the advantages of better adaptability and lightweight.…”
Section: Pneumatic Driven Downforce Adjustment Devicementioning
confidence: 99%